2022
DOI: 10.9734/ejnfs/2022/v14i111265
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Therapeutic Foods on Hematological Parameters of Malnourished Children Admitted at the Intensive Nutritional Recovery Center of Tessaoua, Maradi, Niger Republic

Abstract: Aims: To evaluate the impact of the therapeutic foods on the hematological parameters of malnourished children below 5 years of age. Study Design:  This is a Prospective cross-sectional study. Place and Duration of Study: Intensive Nutritional Recovery Center of Tessaoua, Maradi, Niger republic, from June 15 to September 10, 2022. Methodology: We included 60 malnourished children (36 males, 24 females; age range 6-59 months) who are severely acutely malnourished. Standard survey forms that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Another study has also shown that these antibacterial effects are generally the result of a coordinated action between the different constituents of extracts [24]. Based on these therapeutic virtues in addition to their nutritional ones, these food plants could be useful to fight the malnutrition especially in children who are the first victims [12], since the malnutrition is most often due to the microbial poisoning.…”
Section: Bactericidal and Bacteriostatic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study has also shown that these antibacterial effects are generally the result of a coordinated action between the different constituents of extracts [24]. Based on these therapeutic virtues in addition to their nutritional ones, these food plants could be useful to fight the malnutrition especially in children who are the first victims [12], since the malnutrition is most often due to the microbial poisoning.…”
Section: Bactericidal and Bacteriostatic Propertiesmentioning
confidence: 99%
“…Regarding to the high frequent use of traditional medicine for the primary care by a large part of the population in both developed and developing countries [11], it is then important to extend the investigations on this category of food plants. Nowadays, the therapeutic foods are very coveted to fight strongly against the malnutrition especially in children [12].…”
Section: Introductionmentioning
confidence: 99%